Exploring Sensitized Photon Upconversion – From Past to Present - Colette M. Sullivan; Lea Nienhaus (CHIMIA)
The conversion of low energy photons into high energy photons via triplet-triplet annihilation (TTA) photon upconversion (UC) has become a promising avenue for furthering a wide range of optoelectronic applications. Through the decades of research, many combinations of triplet sensitizer species and annihilator molecules have been investigated unlocking the entire visible spectrum upon proper pairings of sensitizer and annihilator identities. Here, we reflect upon the seminal works which lay the foundation for TTA-UC originating from solution-based methods and highlight the recent advances made within the solid state primarily focusing on perovskite-based triplet generation.